Cara Pandang Masyarakat Kota Cilacap Terhadap Kesadaran Menjalankan Protokol Kesehatan Di Era Pascapandemi Covid-19 - Deyana Luthfy Erianti; Nurhadi Nurhadi; Yuhastina Yuhastina (Universitas Negeri Makassar, 2022)
The Covid-19 pandemic has had a major impact on daily activities, including social interactions in society. Public awareness of health protocols in social interactions during the Covid-19 pandemic focuses on changing activities or behavior with the main goal of not contracting or transmitting the corona virus by adapting activities in the community through the application of health protocols. In the Central Java region, especially Cilacap Regency, the amount of public awareness of health protocols in the era of the Covid-19 pandemic is still relatively low. This study aims to determine the perspective of the people of Cilacap on the awareness of implementing Health protocols in the Covid-19 Pandemic Era. The research was conducted by collecting data through interviews and documentation. The sample in this study is the people of Cilacap city who meet the criteria. After obtaining the data, the validity of the data was tested by triangulation. Meanwhile, for data analysis using Miles and Huberman models. From the research results obtained, the community already has enough knowledge about the importance of implementing Health protocols. In carrying out a health protocol, the people of the city of Cilacap are the most obedient in the use of masks. However, in terms of reducing mobility, maintaining distance, and avoiding crowds, this is still quite difficult to do because it is contrary to activities that are workers and require interaction with other people. The results of this study can be used as an effort to increase public awareness of the importance of health protocols in social interaction.